Transformation of supply chain ecosystems : technological innovations and collaborations - Pandey, Anamika; Al-Turjman, Fadi (Emerald Publishing Limited, 2025)
In today's competitive economy, digital transformation and technology adoption is the most effective strategy for establishing a strong corporation. Technology also plays a significant role in digitalizing supply chain functions and systems. Product complexity and changing customer demands have compelled businesses to use technology to transform supply chain management and assist in monitoring and maintaining visibility throughout the movement of items in the supply chain to increase corporate growth and reduce risk. Using technology in the supply chain processes improves transparency and control over the flow of various functions. Businesses can become more flexible, agile, open, and collaborative due to technological advancements. Transformation of Supply Chain Ecosystems: Technological innovations and collaborations brings together the contributions from the experts in designing and implementing supply chain systems, like inventory and transport management, warehouse operations, analysing customer preferences, and supply chain analytics. This book reflects upon a few untouched segments in the supply chain and logistics domain such as hyper automation, data security, metaverse, RPA and UAV for warehouse operations, and use of Explainable AI (XAI) for robust supply chain ecosystems. This book covers case studies of best practices on how supply chains and logistics functions are implemented in real time in Fortune 100 firms. It also includes examples of implementation frameworks created and used by various sectors for transformation SCM.